Administrative empowerment and its impact on the performance of the institution- Case study: Hasnaoui group in Sidi Bel Abbe - Amina Nadji; Ikram Sabri; Ahlem Naoum (Advanced Research in Economics and Business Strategy Journal)
This study investigated the impact of administrative empowerment on organizational performance at the Hasnaoui group in Sidi Bel Abbes. A sample of 47 individuals was surveyed, and the data were analyzed using statistical methods.